Ukraińskie straty osobowe w dystrykcie lubelskim (październik 1939−lipiec 1944) – wstępna analiza materiału statystycznego - Hałagida, Igor (Pamięć i Sprawiedliwość, 2017)
The article is an attempt at determining the actual casualties of the Ukrainian population in the occupational Lublin District between 1939 and 1944. As a result of the research to date, which is still continued, the search reached for previously unused sources, e.g. archival materials dating from the war, memoirs or press. As a result, the data concerning Ukrainian population: the number of killed, wounded and arrested divided according to specific poviats, years and months as well as perpetrators, has been made more precise. The results thus obtained contradict the thesis about mass murders in the Lublin region in 1942, which supposedly preceded the purge against the Polish that the OUN-B initiated in Volhynia in 1943, which is a statement popular in Ukrainian historiography. On the other hand, the data prove that the operations carried out by the Polish underground in the spring of 1944 (the so-called Hrubieszów Revolution) were much more brutal and led to many more casualties among the civilian population than the Polish historiography had previously stated.